Pré-estresse articular: comparação do comportamento passivo do tornozelo com predições de um modelo duas-molas pré-estressado - Thales Rezende de Souza (2008)
Traditional models of joint stability assume the existence of a joint range of motion where there is negligible or no passive resistance to mechanical perturbations and great dependence on muscle contractions to achieve stability. In contrast, joints in vivo exert passive moments in their entire ranges of motion and the resultant stiffness is explored and used by the motor system to achieve stability in many activities. This passive stability is similar to the intrinsic stability of prestressed mechanical systems, leading to the hypothesis that joints have prestress. The prestress of joints would be held in their elastic structures and would created concurrent passive tension in antagonistic elastic structures (passive co-tension) and opposite passive elastic moments in part of the range of motion. The co-tension resultant from prestress produces greater stiffness and stability, in comparison with systems without this property. The aim of the present study was to investigate the presence of prestress at the ankle joint. A prestressed two-spring model, composed of two nonlinear springs and a massless body, and configured with pre-tension in the springs, generated qualitative predictions about changes in the passive mechanical behavior of the ankle, when the posterior elastic structures of this joint was lengthened. The ankle passive moment, related to displacements in the sagittal plane, was measured in 27 young healthy subjects, using an isokinetic dynamometer. Electromyography was monitored in order to guarantee that the muscles were inactive during the tests. Passive moment was measured with the knee at 90º, 60º, 30º, and 0º of flexion, respectively, in order to lengthen posterior elastic structures of the ankle. The joint position where passive moment is zero (moment-zero), dorsiflexion stiffness, plantar flexion stiffness, and stiffness in the final 5º of plantar flexion were measured. Repeated measures analyses of variance and pre-planned contrasts, with significance levels () of 0.05, were used to compare dependent variables between knee positions. It was found that the lengthening of posterior elastic structures of the ankle generated displacements of the moment-zero toward plantar flexion (p<0.001), increases in the dorsiflexion stiffness (p0.037), increases in the plantar flexion stiffness (p0.001), and increases in the stiffness of final plantar flexion positions (p<0.047). These results are in accordance with the predictions of the model and indicate that there is passive co-tension resultant from the prestress in the elastic structures of the ankle. Furthermore, these changes are analogous to the known responses of prestressed systems when the tension of one or more of its elastic components is asymmetrically increased. Joint resting positions (moment-zero) constitute positions where there is equilibrium between opposite passive elastic moments created by the passive co-tension. Moreover, biarticular posterior elastic structures have great pre-strain. Tissue prestress is a property underlying the net passive moment and stiffness of the ankle and, associated with other passive properties, such as tissue viscosity, provides intrinsic stability to this joint.